ERBB2-CAR-Engineered Cytokine-Induced Killer Cells Exhibit Both CAR-Mediated and Innate Immunity Against High-Risk Rhabdomyosarcoma - Merker, Michael; Wagner, Juliane; Kreyenberg, Hermann; Heim, Catrin; Moser, Laura M.; Wels, Winfried S.; Bonig, Halvard; Ivics, Zoltán; Ullrich, Evelyn; Klingebiel, Thomas; Bader, Peter; Rettinger, Eva (Frontiers in Immunology, 2020)
High-risk rhabdomyosarcoma (RMS) occurring in childhood to young adulthood is associated with a poor prognosis; especially children above the age of ten with advanced stage alveolar RMS still succumb to the disease within a median of two years. The advent of chimeric antigen receptor (CAR)-engineered T cells marked significant progress in the treatment of refractory B cell malignancies, but experience for solid tumors has proven challenging. We speculate that this is at least in part due to the poor quality of the patient’s own T cells and therefore propose using CAR-modified cytokine-induced killer (CIK) cells as effector cells. CIK cells are a heterogeneous population of polyclonal T cells that acquire phenotypic and cytotoxic properties of natural killer (NK) cells through the cultivation process, becoming so-called T-NK cells. CIK cells can be genetically modified to express CARs. They are minimally alloreactive and can therefore be acquired from haploidentical first-degree relatives. Here, we explored the potential of ERBB2-CAR-modified random-donor CIK cells as a treatment for RMS in xenotolerant mice bearing disseminated high-risk RMS tumors. In otherwise untreated mice, RMS tumors engrafted 13 to 35 days after intravenous tumor cell injection, as shown by in vivo bioluminescence imaging, immunohistochemistry, and polymerase chain reaction for human gDNA, and mice died shortly thereafter (median/range: 62/56-66 days, n=5). Wild-type (WT) CIK cells given at an early stage delayed and eliminated RMS engraftment in 4 of 6 (67%) mice, while ERBB2-CAR CIK cells inhibited initial tumor load in 8 of 8 (100%) mice. WT CIK cells were detectable but not as active as CAR CIK cells at distant tumor sites. CIK cell therapies during advanced RMS delayed but did not inhibit tumor progression compared to untreated controls. ERBB2-CAR CIK cell therapy also supported innate immunity as evidenced by selective accumulation of NK and T-NK cell subpopulations in disseminated RMS tumors, which was not observed for WT CIK cells. Our data underscore the power of heterogenous immune cell populations (T, NK, and T-NK cells) to control solid tumors, which can be further enhanced with CARs, suggesting ERBB2-CAR CIK cells as a potential treatment for high-risk RMS.